Cosmos - Gombrowicz, Witold; Borchardt, Danuta, 1930- (New Haven : Yale University Press, 2005)
A dark, quasi-detective novel, ""Cosmos ""follows the classic noir motif to explore the arbitrariness of language, the joke of human freedom, and man's attempt to bring order out of chaos in his psychological life.Published in 1965, ""Cosmos ""is the last novel by Witold Gombrowicz (1904-1969) and his most somber and multifaceted work. Two young men meet by chance in a Polish resort town in the Carpathian Mountains. Intending to spend their vacation relaxing, they find a secluded family-run ""pension. ""But the two become embroiled first in a macabre event on the way to the ""pension, ""then in the peculiar activities and psychological travails of the family running it. Gombrowicz offers no solution to their predicament.""Cosmos ""is translated here for the first time directly from the Polish by Danuta Borchardt, translator of ""Ferdydurke."".
Cosmos -- Translatorâ€?s Note -- Cosmos
Print version record.
English.
eBooks on EBSCOhost
Keywords: Gombrowicz, Witold; Polish literature -- 20th century; Polish fiction; Littérature polonaise -- 20e siècle.; Roman polonais; FICTION -- General; Polish fiction; Polish literature; 1900-1999; Electronic book